Strategy for improving the quality of School Dental Health Efforts at Tabanan Public Health Center - I Gusti Ayu Ari Agung; I Nyoman Panji Triadnya Palgunadi (Faculty of Dental Medicine, Universitas Airlangga https://fkg.unair.ac.id/en, 2022)
Background: The School Dental Health Efforts or Usaha Kesehatan Gigi Sekolah (UKGS) is a public health effort to maintain and improve the dental and oral health of elementary school students. UKGS is the strategy and the flagship of dental health in schools. The implementation of UKGS involves three elements, namely the Public Health Centre or Pusat Kesehatan Masyarakat (Puskesmas), schools, and parents. The three elements in UKGS are the driving force and restraining force, which greatly affect the quality of UKGS services. Purpose: This study aimed to analyze a strategy that can improve the quality of UKGS at Tabanan Puskesmas. Methods: This research used evaluative research and was analyzed by Kurt Lewin’s Force Field Analysis. Results: The driving forces that have the highest score are good knowledge, the skill of personnel, and guidelines for implementing the UKGS at Puskesmas; whereas the restraining forces that have the highest score are the unavailability of guidebooks and health teacher skills, as well as lack of budget for the UKGS activities. Conclusion: Strategies that can improve the quality of UKGS at Tabanan Puskesmas can be done by utilizing the facilities at the Puskesmas for the UKGS activities in schools, transmitting knowledge and skills from Puskesmas officers to the UKGS staff in schools, and increasing the budget by means of self-help.